Accumulation Time and Antioxidant Responses of Inorganic Arsenic on Brown Seaweed Padina minor - Wiga Alif Violando; Sri Andayani; Saou-Lien Wong; Chih-Hsuan Tseng (Research Journal of Life Science, 2017)
Padina minor had a good ability to bind and accumulate arsenic (As). This research aimed to observe the As accumulation and detoxification time, also the antioxidant defense activities. Each gram of P. minor was culture in various As contaminate media for 7 days, then reculture in As-free media for 14 days. There was an acute effect on thali by decreasing its growth slowly till final day with small amount accumulation at concentration 25 µg iAs g-1. Meanwhile, direct attenuation impact was due at 50 and 100 µg iAs g-1 with massive accumulation. The thali starts to recover after reculture in health environment for 14 days. Only As5+ was detected on the thali at day 7 and 21 were indicates internal oxidation of As3+ was done before 7 days. Various antioxidant activities such as decreasing polysaccharide and increasing activities of DPPH and flavonoid at high level were observed. Those indicated that 50 µg iAs g-1 was optimum iAs level on P. minor. The results indicate that P. minor has ability to oxidase and methylate with antioxidant role as defensive activities against iAs, but it also needs more than 14 days to recover in high level contamination.